Equilibrium Model Of Gas Adsorption On Zeolite - Kamarudin, K. S. N.; Hamdan, H.; Mat, H. (2004)
The adsorption of methane and carbon dioxide on NaY, ZSM-5 and beta have been investigated under similar conditions using volumetric adsorption apparatus. The nature of zeolite adsorbing surface is the determining factor in adsorption but the behaviors of molecules adsorb can be easily described in adsorption equilibrium where many equations based on different concept have been proposed. In order to elucidate the experimental data obtained, the adsorption data was fitted using the existing thermodynamic models. The simplest equations are Langmuir and Freundlich, each of which involves two parameters but Henry equation represents the adsorption at low coverage. Another equation that is widely used is Dubinin-Polanyi equation. Based on the model constants, considerable differences in the adsorption of CH4 and CO2 with these zeolites were observed.